Surveying Parents’ Awareness and Adherence to Influenza Vaccination Recommendations in Children in Southern Italy - Gabriella Di Giuseppe; Giovanna Paduano; Sara Vaienna; Giuseppe Maisto; Concetta Paola Pelullo; Maria Pavia (Vaccines, 2022)
Background: This study explored awareness and adhesion of parents to the recommendations for influenza vaccination for their children. Methods: This cross-sectional study was conducted from March to June 2022 among parents of 6 months–6 years-old children in Southern Italy. Results: Only 22.1% of parents were aware that influenza vaccination was recommended for healthy children, and 31.8% reported at least one influenza vaccination in the four influenza seasons from 2018/2019 to 2021/2022. Adherence was higher among parents who had received influenza vaccination at least once, who knew the main childhood vaccinations, who knew that influenza can be prevented, that influenza vaccination is recommended for healthy children, who believe that it is useful, and who have been informed about it by physicians. Willingness to vaccinate their children in the upcoming season was 48.6% and was higher among parents who had vaccinated their children at least once, believed that influenza vaccination protects against severe complications, believed that it is useful, and that it is not better for children to acquire immunization through illness than through vaccination. Conclusions: These findings suggest that efforts should be devoted to educating parents on the risks associated with the disease and the benefits of the vaccine.